Evaluation of sedation and clinical effects of midazolam with ketamine or dexmedetomidine in pet rabbits. (18th October 2014) - Bellini, L.; Banzato, T.; Contiero, B.; Zotti, A.
Abstract : The effects of two sedation protocols combining midazolam with ketamine (ketamine group) or dexmedetomidine (dexmedetomidine group) were studied in dwarf companion rabbits undergoing abdominal ultrasound scan. The onset of sedation was faster in the ketamine group; a few rabbits in the dexmedetomidine group required additional doses to lose the righting reflex, although sedation time was not different between groups. A semi‐quantitative scale was used to score sedation quality, which was higher in rabbits that received dexmedetomidine rather than ketamine. Pulse rate was lower in the dexmedetomidine group (206 vs 240 bpm), although Doppler blood pressure was higher than in the ketamine group (109 vs 89 mm Hg). Respiratory rate decreased in relation to the baseline values with both protocols but arterial haemoglobin saturation with oxygen was maintained similar to the pre‐sedation values throughout the entire procedure, regardless of protocol used and without oxygen supplementation. Both protocols allowed performance of ultrasound scanning, although dexmedetomidine may be preferred if a deep sedation level is required.